Widow's Tale, A 1884-1896 Diary of Helen Mar Kimball Whitney - Hatch, Charles (Utah State University Press, 2003)
Volume 6, Life Writings of Frontier Women series, ed. Maureen Ursenbach Beecher Mormon culture has produced during its history an unusual number of historically valuable personal writings. Few such diaries, journals, and memoirs published have provided as rich and well rounded a window into their authors' lives and worlds as the diary of Helen Mar Kimball Whitney. Because it provides a rare account of the widely experienced situations and problems faced by widows, her record has relevance far beyond Mormon history though. As a teenager Helen Kimball had been a polygamous wife of Mormon founder Joseph Smith. She subsequently married Horace Whitney. Her children included the noted Mormon author, religious authority, and politician Orson F. Whitney. She herself was a leading woman in her church and society and a writer known especially for her defense of plural marriage. Upon Horace's death, she began keeping a diary. In it, she recorded her economic, physical, and psychological struggles to meet the challenges of widowhood. Her writing was introspective and revelatory. She also commented on the changing society around her, as Salt Lake City in the last decades of the nineteenth century underwent rapid transformation, modernizing and opening up from its pioneer beginnings. She remained a well-connected member of an elite group of leading Latter-day Saint women, and prominent Utah and Mormon historical figures appear frequently in her daily entries. Above all, though, her diary is an unusual record of difficulties faced in many times and places by women, of all classes, whose husbands died and left them without sufficient means to carry on the types of lives to which they had been accustomed.